Supranational emergency politics? What executives' public crisis communication may tell us - Christian Rauh (Journal of European Public Policy, 2022)
This contribution engages with the empirical analysis of emergency politics in the EU, arguing that executives' public communication helps to distinguish crisis management from crisis exploitation. An initial, descriptive text analysis of emergency emphasis in more than 19,000 executive speeches suggests that supranational actors, most notably the European Central Bank, do indeed use rather alarmist language over and beyond objective crisis pressures when their competences are contested. Yet, this behaviour does not appear to be a ubiquitous phenomenon, pointing to the need for more specific expectations on when and why EU executives pro-actively embark on the emergency politics script.
doi: 10.7910/DVN/M2QFGM
Keywords: 300; emergency politics; European Union (EU); political communication; European Central Bank; European Commission; text analysis